Titanium coil heat treatment method
Through the vacuum annealing method of titanium coils with multi-stage heating and insulation, the problems of uneven mechanical properties and poor surface quality of titanium coils are solved, and the high performance and uniform moldability of titanium coils are achieved, meeting the requirements of high-end applications.
Patent Information
- Application Number
- CN202411410460.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
The vacuum annealing method of existing titanium coils leads to uneven mechanical properties and poor surface quality, which cannot meet the moldability requirements of high-end applications, and the reduction of thermal conductivity leads to uneven thermal treatment, resulting in poor grain size and fluctuations in mechanical properties.
The vacuum annealing method of titanium coils using multi-stage heating and insulation, including controlling the heating rate, insulation temperature and vacuum degree, and protecting it by inert gas to ensure uniformity and cleanliness of titanium coils during each heating and cooling process. Use argon and circulating fans to remove impurity gases and gradually increase the temperature to promote recrystallization and uniform grain growth.
It significantly improves the uniformity of the transverse and longitudinal mechanical properties of the titanium coil, reduces the anisotropy, improves the moldability and surface quality, and ensures the high performance and good economic benefits of the titanium coil with a thickness of less than 3mm.
Smart Images

Figure CN119287292A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloys, and relates to a vacuum annealing method for a titanium coil with a thickness specification of less than 3 mm, in particular to a titanium coil heat treatment method. Background Art
[0002] Titanium is one of the lightest metal structural materials, with a density of 2 / 3 of that of steel. It has good corrosion resistance to seawater and chlorine environments and is widely used in aviation, aerospace, medical and high-end industrial applications. However, the large-scale application of high-end titanium and its alloys is limited by its long process flow, small width, low yield rate, poor formability, and poor surface quality. The production process of titanium coils is: alloy batching - electrode block pressing - VAR smelting - forging blanking - hot rolling - pickling - cold rolling - degreasing - vacuum annealing - packaging - delivery. Vacuum annealing is the last step in adjusting the mechanical properties, and its annealing method directly determines the final mechanical properties of the product.
[0003] After heat preservation annealing above the recrystallization temperature, the titanium plate can eliminate work hardening, equiaxed grains and restore plasticity, making it have good formability. At present, the difference in the transverse and longitudinal mechanical properties (yield strength) of vacuum annealed titanium coils at home and abroad is about 30 to 50 MPa, which cannot meet the high formability performance required in the field of high-end titanium. The thickness of cold-rolled titanium coils annealed in a vacuum furnace is generally less than 3 mm. The thermal conductivity of titanium is λ = 15.24W / (m·K), which is about 1 / 4 of nickel, 1 / 5 of iron, and 1 / 14 of aluminum, while the thermal conductivity of various titanium alloys is about 50% lower than that of titanium. The radial direction of the titanium coil is a multi-layer thin titanium superposition heat transfer, and its heat transfer mode is mainly interlayer heat conduction. The axial and circumferential directions are heat transfer by the titanium matrix. The radial thermal conductivity decreases with the thinning of the titanium plate, and its value is about 15% to 25% of the axial and radial directions. Studies have shown that the radial thermal conductivity is affected by the surface roughness of the coil and the coil curling tension. When the titanium coil is heated, the outer ring is heated faster, the temperature difference between the inner and outer diameters is large, and the head and tail are heated unevenly, resulting in grain size differences and large fluctuations in mechanical properties. In addition, the temperature is also uneven during heating and cooling. When heating, the outer ring is heated and expanded quickly, the inner ring temperature is low, and the tensile stress is concentrated; when cooling, the outer ring is cooled and contracted, and the inner ring is a high temperature area, the compressive stress is concentrated, and repeated tensile and compressive stresses form large internal stresses, resulting in defects such as poor coil shape, poor plate shape, and difficulty in straightening, which affect sales. In addition, titanium has active chemical properties. Although vacuum annealing exhausts the air in the furnace before heating, it is heated in a low vacuum state. At high temperatures, it is easy to react with a small amount of O, H, N and other elements in the air to form an oxide layer, and react with residual chemicals in the previous process such as rolling oil and emulsion, forming annealing black spots in a high temperature atmosphere, and the outer ring is seriously bonded, affecting the surface quality of the titanium coil.
[0004] In summary, strictly controlling the vacuum annealing system can improve the comprehensive properties of titanium and titanium alloys, which is of great significance to promoting and expanding the application of titanium. Summary of the invention
[0005] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a method for vacuum annealing of titanium alloy strips, and proposes a heating method for vacuum annealing of titanium strips, including heating rate, holding temperature, holding time, vacuum degree, protective gas control, etc., to finally prepare a wide titanium strip with a width of 1500-2000mm, a thickness of 0.3-3mm, and good surface quality. The difference in yield strength between the transverse and longitudinal directions is less than 10MPa, and the difference in elongation after fracture is less than 3%. This solves the problem of large anisotropy of existing titanium strips after annealing, greatly improves product quality, increases product added value, and has good economic benefits.
[0006] In order to achieve the above-mentioned invention object, the present invention provides a titanium coil heat treatment method, the process flow includes: surface treatment of titanium coil with thickness of 0.3-3mm - loading into furnace - introducing inert gas to wash furnace - heating once - keeping warm once - stopping ventilation - vacuuming - heating twice - keeping warm twice - heating three times - keeping warm three times - cooling - keeping warm - cooling - removing vacuum - taking out of furnace; the method includes the following steps:
[0007] ① Roll the raw titanium coil on the 18-roller cold rolling mill by controlling the last cold rolling work roll, and roll the original titanium coil to the target thickness of 0.3-3mm, the last work roll roughness of 4-8μm, and the last deformation of 8%-12%; the deformation of 8%-12% and the work roll roughness of 4-8μm are conducive to improving the surface roughness of the titanium coil, enhancing the surface lubricity, and avoiding interlayer adhesion during annealing. The titanium coil with a thickness of 0.3-3mm is degreased and curled, and the curling tension is controlled at 10-18kN. After curling, it is loaded into the bedroom vacuum furnace in sequence. A thermocouple is installed at the bottom of each titanium coil and pressed tightly. The number of titanium coils annealed in each furnace is ≥3 coils. The surface of the titanium coil is a hot-rolled pickled surface or a clean and bright surface after degreasing and degreasing after cold rolling. The spacing between coils is controlled to be 100-200mm. The space of the vacuum furnace is limited. If the spacing is too large, it will affect the number of single batch annealing. If the spacing is too small, the adjacent titanium coils will be locally heated by radiation, affecting the uniformity of the temperature field of the titanium coils and the uniformity of the structure after annealing. The curling tension is controlled at 10-18kN. If the tension is too small or too large, it will easily lead to poor coil shape. If the tension is too large, it will easily cause adhesion, affecting the surface quality of the titanium coil.
[0008] ② First heating: Start heating from room temperature to 250℃, keep warm for 10~16h, the heating rate v is determined by the thickness of the annealed titanium coil v=s*d, where s is the thickness heating compensation coefficient s=40~60℃ / h·mm, d is the thickness of the annealed titanium coil. When the thickness is less than 1mm, take the lower limit of 40℃ / h·mm; when the thickness is 1~2mm, take the value of 50℃ / h·mm; when the thickness is 2~3mm, take the value of 60℃ / h·mm. After the insulation is completed, start vacuuming, the vacuum degree ≤4×10 -2 Pa and then the temperature is raised. This stage is a low-temperature operation stage, which is conducive to exhausting impurity gases in the furnace and ensuring cleanliness.
[0009] ③At the beginning of the first heating, 20-60L / min argon gas is introduced to clean the furnace. A circulating fan is installed in the furnace. The wind direction of the fan is on the same side as the argon gas. The fan is started while the argon gas is introduced. This is beneficial to remove impurity gases and avoid chemical reactions with the surface of the titanium coil to cause interlayer adhesion.
[0010] ④ The second heating: maintain vacuum degree ≤4×10 -2 Pa, heated to 480℃, kept warm for 20 to 24h, the heating rate v is determined by the thickness of the annealed titanium coil v=s*d, where s is the thickness heating compensation coefficient s=20~40℃ / h·mm, and d is the thickness of the annealed titanium coil. When the thickness is less than 1mm, take the lower limit of 20℃ / h·mm; when the thickness is 1 to 2mm, take the value of 30℃ / h·mm; when the thickness is 2 to 3mm, take the value of 40℃ / h·mm. Conventional titanium coils are annealed after cold rolling and hot rolling deformation, and their recrystallization temperature is generally less than 500℃. By slowly heating to 480℃, it is prepared for the simultaneous recrystallization of different parts of the titanium coil in the next stage.
[0011] ⑤The third heating: keep the vacuum degree ≤4×10 -2Pa, heat to 570℃~610℃ at a heating rate of 10~20℃ / h, and keep warm for 16~24h; after the insulation, reduce the temperature to 550℃ at a cooling rate of 10~20℃ / h, and continue to keep warm for 24~32h. After the insulation, reduce the temperature to 400℃ at a cooling rate of 10℃ / h, cut off the heating power, press the thermocouple temperature to 200℃, introduce argon to reduce the vacuum, and open the furnace door when the thermocouple temperature is 120℃ for natural cooling. At a lower heating rate, when a certain temperature is reached, the titanium coil gradually recrystallizes from the outside to the inside, and the outer coil temperature is higher. At this time, it is slowly reduced to 550℃. The temperature difference between the inside and the outside is used to transfer heat to the inner circle to balance the internal and external stresses, ensuring temperature uniformity while avoiding poor plate shape caused by thermal stress. When the temperature drops to 400℃ after the insulation is completed, the outer surface temperature drops rapidly, and the temperature of the outer ring of the titanium coil is approximately equal to 400℃. At this time, the residual heat of the inner ring is continuously used as the driving force for recrystallization, extending the insulation time of the titanium coil area where recrystallization does not occur, so as to obtain a uniform titanium coil with an average grain size difference of less than 10μm throughout the coil.
[0012] ⑥ After annealing, the titanium coil is sampled for tensile test and metallographic inspection. The transverse and longitudinal mechanical properties are uniform. The tensile specimens are prepared and tested in accordance with GB / T 228.1-2021. The yield strength difference is less than 10MPa, the elongation after fracture is less than 2%, the anisotropy is significantly eliminated, the average grain size fluctuation in different parts is less than 10μm, and the grain size is uniform.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The invention solves the problem that the existing titanium coil has large anisotropy during vacuum annealing, improves the performance uniformity of titanium and titanium alloy coils, improves the formability of titanium materials to a great extent, has good comprehensive performance, and has good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The metallographic structure diagram of the head of the finished titanium coil sample obtained in the embodiment;
[0016] Figure 2 The metallographic structure diagram of the tail of the finished titanium coil sample obtained in the embodiment;
[0017] Figure 3 The following are the transverse and longitudinal stretching curves of the titanium coil product obtained in the example. DETAILED DESCRIPTION
[0018] The present invention is further described below in conjunction with specific examples, but the present invention is not limited in any way. To avoid redundant description, the raw materials in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.
[0019] A titanium coil heat treatment method comprises the following steps:
[0020] ① Roll the raw titanium coil to the target thickness of 0.3-3mm on the 18-roller cold rolling mill by controlling the last cold rolling work roll, and the last deformation is 8%-12%; then degrease the titanium coil and curl it, and control the curling tension to 10-18kN. After curling, load it into the bedroom vacuum furnace in sequence, and install a thermocouple at the bottom of each titanium coil and press it tightly. The number of annealed titanium coils in each furnace is ≥3;
[0021] ② The first heating: from room temperature to 250℃, keep warm for 10-16h, the heating rate is determined by the thickness of the annealed titanium coil; after the end of the heat preservation, vacuum is drawn, the vacuum degree is ≤4×10 -2 Pa and then subsequent heating;
[0022] ③At the beginning of the first heating, argon gas of 20-60L / min is introduced to clean the furnace. A circulating fan is installed in the furnace. The wind direction of the fan is on the same side as the argon gas. The fan is started while the argon gas is introduced;
[0023] ④ The second heating: maintain vacuum degree ≤4×10 -2 Pa, heated to 480℃, kept warm for 20-24h, the heating rate is determined by the thickness of the annealed titanium coil;
[0024] ⑤The third heating: keep the vacuum degree ≤4×10 -2 Pa, heat to 570℃~610℃ at a heating rate of 10~20℃ / h, and keep warm for 16~24h; after the insulation, reduce the temperature to 550℃ at a cooling rate of 10~20℃ / h, and continue to keep warm for 24~32h; after the insulation, reduce the temperature to 400℃ at a cooling rate of 10℃ / h, cut off the heating power, press the thermocouple temperature to 200℃, introduce argon to reduce the vacuum degree, and when the thermocouple temperature reaches 120℃, open the furnace door and cool naturally;
[0025] ⑥ After annealing, the titanium coil is sampled for tensile test and metallographic inspection. The transverse and longitudinal mechanical properties are uniform. The tensile specimens are prepared and tested in accordance with GB / T 228.1-2021. The yield strength difference is less than 10MPa, the elongation after fracture is less than 2%, the anisotropy is eliminated, and the average grain size fluctuation in different parts is less than 10μm.
[0026] The matters not described in the following embodiments are the same as the description of the above specific implementation methods.
[0027] Example
[0028] A titanium coil heat treatment method, the specific process flow is:
[0029] ① The raw titanium coil is rolled on the 18-roller cold rolling mill by controlling the last cold rolling work roll, and the original titanium coil is rolled to the target thickness of 0.5mm, the last work roll roughness is 4μm, and the last deformation is 8%. The titanium coil with a thickness of 0.5mm is degreased on the surface and then curled. The curling tension is controlled at 10kN. After curling, it is loaded into the bedroom vacuum furnace in sequence. A thermocouple is installed at the bottom of each titanium coil and pressed. The number of annealed titanium coils is 4. The surface of the titanium coil is a hot-rolled pickled surface or a clean and bright surface after degreasing and degreasing after cold rolling. The spacing between coils is controlled to be 100mm.
[0030] ② First heating: Start heating from room temperature and heat up to 250℃ at a heating rate of 40℃ / h. During the heating process, introduce a large flow of argon gas to wash the furnace. The furnace is equipped with a circulating fan, and the fan wind direction is on the same side as the argon gas. Start the fan while introducing argon gas. When it reaches 250℃, keep it warm for 10h. After the end of the heat preservation, start vacuuming. The vacuum degree is ≤4×10 -2 Pa and then the temperature is raised.
[0031] ③At the beginning of the first heating, 60L / min argon gas is introduced to clean the furnace. A circulating fan is installed in the furnace. The wind direction of the fan is on the same side as the argon gas. The fan is started while the argon gas is introduced.
[0032] ④ The second heating: maintain vacuum degree ≤4×10 -2 Pa, heat to 480℃ at a heating rate of 20℃ / h and keep warm for 20h.
[0033] ⑤The third heating: keep the vacuum degree ≤4×10 -2 Pa, heated to 570℃ at a heating rate of 10℃ / h, kept at this temperature for 16h, cooled to 550℃ at a cooling rate of 10℃ / h after the end of the insulation, and kept at this temperature for 24h. After the end of the insulation, cooled to 400℃ at a cooling rate of 10℃ / h, and a thermocouple was installed at the bottom of the titanium coil every other coil, and pressed tightly. When the pressed thermocouple was 400℃, the heating power was cut off. When the pressed thermocouple was 200℃, argon was introduced to reduce the vacuum degree. When the pressed thermocouple was 120℃, the furnace door was opened for natural cooling.
[0034] ⑥ Take samples of the titanium coil after annealing for tensile test. Prepare and test the tensile specimens according to GB / T 228.1-2021. The tensile curve (engineering stress-engineering strain) is shown in Figure 3 , Transverse mechanical properties: R p0.2 =230Mpa, R m =323Mpa, A=40%, longitudinal mechanical properties: R p0.2 =221Mpa, R m=333Mpa, A=39.5%, the transverse and longitudinal mechanical properties are uniform, and anisotropy is basically eliminated. The results of the titanium coil head and metallographic examination after annealing are as follows Figure 1 and Figure 2 As shown, the grain size is uniform, and the average grain size is 10μm.
[0035] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A titanium coil heat treatment method, characterized in that: The method comprises the following steps: ① Roll the raw titanium coil to the target thickness of 0.3-3mm on the 18-roller cold rolling mill by controlling the last cold rolling work roll, and the last deformation is 8%-12%; then degrease the titanium coil and curl it, and control the curling tension to 10-18kN. After curling, load it into the bedroom vacuum furnace in sequence, and install a thermocouple at the bottom of each titanium coil and press it tightly. The number of annealed titanium coils in each furnace is ≥3; ② The first heating: from room temperature to 250℃, keep warm for 10-16h, the heating rate is determined by the thickness of the annealed titanium coil; after the end of the heat preservation, vacuum is drawn, the vacuum degree is ≤4×10 -2 Pa and then subsequent heating; ③At the beginning of the first heating, 20-60L / min argon gas is introduced to clean the furnace. A circulating fan is installed in the furnace. The wind direction of the fan is on the same side as the argon gas. The fan is started while the argon gas is introduced; ④ The second heating: maintain vacuum degree ≤4×10 -2 Pa, heated to 480℃, kept warm for 20-24h, the heating rate is determined by the thickness of the annealed titanium coil; ⑤The third heating: keep the vacuum degree ≤4×10 -2 Pa, heat to 570℃~610℃ at a heating rate of 10~20℃ / h, and keep warm for 16~24h; after the insulation, reduce the temperature to 550℃ at a cooling rate of 10~20℃ / h, and continue to keep warm for 24~32h; after the insulation, reduce the temperature to 400℃ at a cooling rate of 10℃ / h, cut off the heating power, press the thermocouple temperature to 200℃, introduce argon to reduce the vacuum degree, and when the thermocouple temperature reaches 120℃, open the furnace door and cool naturally; ⑥ After annealing, the titanium coil is sampled for tensile test and metallographic inspection. The transverse and longitudinal mechanical properties are uniform. The tensile specimens are prepared and tested in accordance with GB / T 228.1-2021. The yield strength difference is less than 10MPa, the elongation after fracture is less than 2%, the anisotropy is eliminated, and the average grain size fluctuation in different parts is less than 10μm.
2. The heat treatment method according to claim 1, characterized in that Step ① The roughness of the working roll of the final cold rolling is 4-8 μm, the surface of the titanium coil is a hot-rolled pickled rough surface or a clean and bright surface after degreasing and degreasing after cold rolling, and the spacing between the titanium coils is controlled to be 100-200 mm.
3. The heat treatment method according to claim 1, characterized in that In step ②, the heating rate v=s*d, wherein s is the thickness heating compensation coefficient s=40-60°C / h·mm, and d is the thickness of the annealed titanium coil; when the thickness is less than 1 mm, the lower limit value is 40°C / h·mm; when the thickness is 1-2 mm, the value is 50°C / h·mm; when the thickness is 2-3 mm, the value is 60°C / h·mm.
4. The heat treatment method according to claim 1, characterized in that: In step ④, the heating rate v=s*d, wherein s is the thickness heating compensation coefficient s=20-40°C / h·mm, and d is the thickness of the annealed titanium coil; when the thickness is less than 1 mm, the lower limit value is 20°C / h·mm; when the thickness is 1-2 mm, the value is 30°C / h·mm; when the thickness is 2-3 mm, the value is 40°C / h·mm.
Citation Information
Cited By
Method for rolling wide titanium belt at low cost through 18-roller single-stand rolling mill
CN120790660A
A method for low-cost rolling of wide titanium strip using an 18-roll single-stand mill
CN120790660B